1991
DOI: 10.1007/bf01968963
|View full text |Cite
|
Sign up to set email alerts
|

Pathogenesis and reversibility of retinopathy induced by 1,4-bis (4-aminophenoxy)-2-phenylbenzene (2-phenyl-APB-144) in pigmented rats

Abstract: Pigmented male rats were administered a suspension of 0, 25, or 100 mg/kg 2-phenyl-APB-144 in corn oil by gavage. The rats were killed at 4 and 12 h, and at 1, 2, 4, 7, 14, 28, 57, or 84 days after a single oral administration. The primary site of retinopathy appeared to be the retinal pigment epithelial (RPE) cells. The RPE cells showed necrosis within 12 h post-exposure (PE) at 25 mg/kg and within 4 h PE at 100 mg/kg. Subsequently, photoreceptor outer segments (POS) were disrupted with a hyperplastic RPE cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

1998
1998
2015
2015

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 29 publications
0
15
0
Order By: Relevance
“…Therefore, endogenous Hsp90 plays an indispensable role in homeostasis of the retina. Several reports showed that photoreceptors are the primary components of phototransduction (Bonting et al, 1961;Fox et al, 1997), and that structural disorder of photoreceptor cells was irreversible (Lee and Valentine, 1991). Therefore, inhibition of Hsp90 might lead to irreversible retinal damage.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, endogenous Hsp90 plays an indispensable role in homeostasis of the retina. Several reports showed that photoreceptors are the primary components of phototransduction (Bonting et al, 1961;Fox et al, 1997), and that structural disorder of photoreceptor cells was irreversible (Lee and Valentine, 1991). Therefore, inhibition of Hsp90 might lead to irreversible retinal damage.…”
Section: Discussionmentioning
confidence: 99%
“…Various pharmacological agents are known to affect the RPE cells primarily [10,17] or to affect the neurosensory retina and damage the RPE secondarily [2,7,16]. When the physiological functions of the RPE are altered, the overlying retina is also affected and results in decrease of visual function.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, with 1,4-bis (4-amynophenoxy)-2phenylbenzene (2-phenyl-APB-144), RPE necrosis is the primary site of toxicity with subsequent photoreceptor outer segment disruption. 10 Although the final event in all cases is the photoreceptor cell degeneration, the primary target differs with each model.…”
Section: Introductionmentioning
confidence: 99%